2022
DOI: 10.1039/d2nh00041e
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably enhanced dynamic oxygen migration on graphene oxide supported by copper substrate

Abstract: The dynamic covalent properties of graphene oxide (GO) are of fundamental interest to a broad range of scientific areas and technological applications. It remains a challenge to access the feasible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The presence of chemisorbed oxygen on the pristine surface of 2D materials tunes the bandgaps [15][16][17], provides active sites for chemical reactions [18] and assists the surface functionalization [19], sometimes is related to the structural degradation and breakdown [20,21]. Furthermore, we found that the chemisorbed oxygen groups can surprisingly convert carbon-based materials, such as graphene and carbon nanotube, into dynamic covalent materials [22][23][24] and even induce the self-adaptivity in response to the adsorption of biomolecules [22]. Although the atomic-thick 2D materials have a large surface-volume ratio and are prone to show high surface reactivity, the O2 dissociation on the surface of 2D materials usually depends on the chemical bonding characteristics, thus differs from one to another [14,25,26].…”
Section: Introductionmentioning
confidence: 80%
“…The presence of chemisorbed oxygen on the pristine surface of 2D materials tunes the bandgaps [15][16][17], provides active sites for chemical reactions [18] and assists the surface functionalization [19], sometimes is related to the structural degradation and breakdown [20,21]. Furthermore, we found that the chemisorbed oxygen groups can surprisingly convert carbon-based materials, such as graphene and carbon nanotube, into dynamic covalent materials [22][23][24] and even induce the self-adaptivity in response to the adsorption of biomolecules [22]. Although the atomic-thick 2D materials have a large surface-volume ratio and are prone to show high surface reactivity, the O2 dissociation on the surface of 2D materials usually depends on the chemical bonding characteristics, thus differs from one to another [14,25,26].…”
Section: Introductionmentioning
confidence: 80%
“…84,93,94 GO supported by a copper substrate (GO@copper) is also expected to show the long-range dynamic characteristic. 76 For graphene, the copper substrate is the most used due to the low solubility of carbon into copper and the well-matched lattice structure. 95 The Cu(111) facet contributes to the fast growth of stable and large-area graphene.…”
Section: Metal-substrate Supportmentioning
confidence: 99%
“…In this minireview, a discussion regarding the realization of long-range migration of chemical compositions along the interfaces of GO-based materials via the spatially connected and consecutive occurrence of DCB-based reversible covalent reactions is presented, and the interfaces are termed “LDCIs”. The effective strategies to realize the GO-based LDCIs, such as water adsorption, 74 interfacial curvature 75 and metal–substrate support, 76 are presented. Moreover, the applications in water dissociation 77 and humidity sensing, 78 and an outlook on potential strategies on other 2D carbon-based materials with different interfacial morphologies 79 or element doping 80 is also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the oxygen-related dynamic behavior at the interface of two-dimensional (2D) materials is of fundamental importance for the advancements of dynamic covalent materials [1][2][3][4][5] and the innovations of technological applications in sensors, 6,7 coatings, [8][9][10][11] and batteries. [12][13][14] As a widely used carbon-based 2D material, graphene oxide (GO) has oxygencontaining functional groups such as epoxy and hydroxyl in abundance, on its basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…20 Even without water, the spontaneously dynamic oxygen migration can still be observed at the interface of carbon nanotubes 21 or be remarkably enhanced on the copper-substrate supported GO. 5 These previous works all concern the carbon-based materials with periodic hexagonal rings; however, whether the dynamic oxygen migration on those with hybrid carbon rings can be accessed remains unknown.…”
Section: Introductionmentioning
confidence: 99%